O conceito de currículo oculto em artigos publicados na biblioteca eletrônica SciELO (2001 - 2015) - Castro, Mariângela Machado de (2017)
This Master's Dissertation is structured around the following question: What the scientific articles published in the SciELO electronic library from 2001 to 2015 reveal when they address the hidden curriculum concept? As a general objective, the study intends to analyze the selected articles in order to verify if they attribute to the hidden curriculum a negative function, or if they also indicate the possibility that it serves the human emancipation. The adopted theoretical framework understands that there are implicit actions, positive or negative, in the relations between curriculum and power that aim to maintain order, contributing to the world vision of the ruling class to prevail. Such actions concern the hidden curriculum and contribute to the hegemony of the ruling class. This curriculum is composed of aspects that exist in school that collaborate tacitly to relevant social learning. Therefore, there is an intrinsic relationship between education and broader aspects of society. However, the hidden curriculum can also act in the sense of human emancipation. It is argued that, in addition to the reproduction of dominant interests, there are conflicts, contradictions and resistance in schools. It is necessary, therefore, to go beyond the reproductive role of the hidden curriculum so that the dialectical movement of reality is evidenced, contributing to social equality. In this sense, the research, of a bibliographic nature, has as corpus of analysis 22 articles published in 19 journals indexed in the SciELO database. Regarding the researched data, it is noteworthy that most of the publications focus on the area of Health. It is verified that most of them refers to Higher Education. Therefore, it is noticed that there is a shortage of articles related to Basic Education and, above all, to the area of Education. In addition, there are no publications of papers in journals specialized in curriculum. The most emphasized aspects in most texts about the approach to the hidden curriculum concept are: i) emphasis on its negative function; ii) its influence on the students' training process; iii) concern of researchers from the area of Health with the teaching of ethics and with the role of the professor; iv) association of the hidden curriculum concept with the disagreement between what is said and what is done; v) relationship between curriculum and economic aspects. The results and characteristics of the studies suggest the existence of a lack of definition of the concept of hidden curriculum, because there is a great dispersion in what is considered this curriculum in the analyzed articles. Most of the works are based on the complaint of the hidden curriculum. However, there are references to the possibility of using this concept for social transformation. It becomes substantial to redefine and resituate the concept of hidden curriculum. It is necessary to go beyond its negative function, using its positive potential for human emancipation, considering it in the dialectical perspective. It is argued, therefore, that the hidden curriculum means a possibility of emancipatory action in the school environment. There is a challenge for everyone involved in education. Consequently, there is much to build towards a fair, democratic and egalitarian education.